Understanding the underlying principles of Masjid architecture through study of built form in place, time, people and culture in demysitifying Islamic architecture - Mohd Nawawi, Norwina; Jahn Kassim, Puteri Shireen; Soomro, Ali Raza; Mustafa, Adibah; Md Nordin, Nurhana; Ishak, Husna (2010)
Masjid or mosque has been typecast as a building typology to represent the presence of Muslim in all parts of the world heedlessly. While the generic symbolism of Masjid as icon to Muslim lies in the definitive domes, arches and minarets, the definitions and abstract implications of Masjid in the Quran and the traditions of the Prophet S.A.W., do not directly addressed the issue physically. While the Masjid signify Islamic architecture to the mass, i.e. Muslim and Non Muslim alike, the architecture fraternity, on the other hand, remain indignant to understand the underlying principles that makes a Masjid a Masjid. The study through primary and secondary data extract from literary and architectural research, interviews significantly disclose the real Masjid as it should be known, to the additions and layers it has been camouflaged with while the history unfold. The study’s objective is to demystify Islamic architecture at its very core-the Masjid. If the world, as the Quran quoted the Masjid, as every place on earth, then no matter whatever built form or architecture it assumes, if it is use as a Masjid, it is a Masjid in whatever name or form it portray. Wallahualam.